Application of space vector pulse width modulation algorithm based on programmable logic array in power system - Cheng, Zhihai; Liu, Hui (Journal of physics. Conference series, 2021)
In the traditional power system, the voltage regulation and frequency modulation control method used for boiler induced draft fan is limited in control accuracy. With the improvement of furnace pressure change accuracy, higher requirements are put forward for motor control algorithm. This paper studies permanent magnet synchronous motor (PMSM) as the executive part of induced draft fan servo control system, and adopts FOC control method based on space vector pulse width modulation (SVPWM). Firstly, the simulation model of SVPWM pulse width modulation algorithm is established by MATLAB to provide theoretical support for the subsequent debugging algorithm; When using FPGA to realize SVPWM modulation algorithm, FPGA has the advantages of high reliability and high real-time processing, which provides theoretical support and application guidance for the realization of high-precision motor control of boiler induced draft fan in power system.